Properties of Sand Cement Brick Containing Quarry Dust (SCBQD) and Bacteria Strain - J.M. , Irwan; Othman, N.; Koh, H.B. (International Journal of Sustainable Construction Engineering and Technology, 2020)
Sand cement brick among favorable building material for low cost house construction due to its low price. Technology development in building material already explored varies waste to be added in improving properties of building materials. Beside that addition of bacteria in building material also proven in literature to improve its properties. In this research addition of bacteria in the cement sand block containing quarry dust (SCBQD) was studied. Several properties namely, compressive strength, depth of carbonation, initial rate of suction (IRS) and water absorption were studied. SCBQD is made from sand, cement, quarry dust and chipping using industrial mix design. In this study, 3% of Enterococcus faecalis (EF) and 5% of Bacillus sp (BSP) bacteria was added in the SCBQD mixes. Three SCBQD mixes were prepared including the control mix without bacteria, SCBQD with 3% EF and SCBQD with 5% BSP. Natural fine aggregate was replaced partially with the quarry dust. 100 mm SCBQD cubes were used to conduct compressive strength, depth of carbonation, initial rate of suction and water absorption test at 7, 14 and 28 days. The experimental results showed that the compressive strength value of SCBQD with addition of bacteria was increased for all curing ages. At 28 days of curing, the compressive strength value for control SCBQD containing quarry without any addition of bacteria is 3.30 MPa, while SCBQD containing quarry dust with addition of 3% of EF bacteria is 3.57 MPa and for SCBQD with 5% of BSP bacteria the value is 4.90 MPa. On the other hand, SCBQD containing 3% EF and 5% BSP gained lower IRS and carbonation depth. Depth of carbonation at 28 days was decreased 9.3% and 20% for SCBQD containing 3% EF and 5% BSP, respectively. Meanwhile, 28-day IRS was reduced 12.9% and 22.6% for SCBQD containing 3% EF and 5% BSP, respectively. In overall, the result shows that, SCBQD with 5% BSP as proven positive and better results when compared to control SCBQD and SCBQD with 3% EF bacteria which is absorb of 12.02% in water absorption. The findings showed that bio-SCBQD containing industrial waste and bacteria has good potential to be used as building material.